James Holmes correspondence - Holmes, James, active 1832.
ALS (1832 July 10) from Holmes of Martyn, Chickasaw Nation, to his mother, Rebecca Boden, of Carlisle, Pa., describing his trip west from New York State to the Chickasaw Nation and discussing government policy of the Andrew Jackson presidential administration in relation to the Five Civilized Tribes.
Missionary to the Chickasaw Nation.
Collection material in English.
Keywords: Boden, Rebecca, -- active 1832.; Jackson, Andrew, -- 1767-1845.; Five Civilized Tribes; Indians of North America -- Government relations; Chickasaw Nation; United States -- Description and travel; Missionaries